Rancang Bangun Aplikasi Prototype Perhitungan Analisa Kelayakan Investasi Pada Bisnis Waralaba (Studi Kasus Pada Royal Crepes Surabaya) - Susilo, Rahmat Ade; Widodo, Arifin Puji; Rahardianto, Panca (Jurnal JSIKA, 2012)
Now, franchise business in Indonesia are growing than before, especially culinary franchise business that is currently increasingly in demand. But not the least of the franchise that failed. Factors affecting the failure of the franchise that is not all people understand about how to calculate and analyze the feasibility of the investment before the opening of business because everyone has different educational and not everyone can analyze the feasibility of the investment. By utilizing information technology, then made ​​an application prototype information system feasibility analysis of investment calculations that can help the franchisee in calculating the BEP and ROI Feasibility and Investment Analysis. The information system is expected to generate output in the form of the cost of production reports to determine the cost of production to be sold, the report projected income statement to calculate the net income derived, Break Event Point report to find out how many units must be sold so that all costs can be covered, the report return on investment to know the percentage of results obtained, and investment feasibility analysis report to see feasibility an investment in a franchise business. Implementation of this system provides information for the franchisee who will calculate the feasibility of an investment of a business franchise that will be executed.   Keywords : Harga pokok produksi, Net Profit, Break Event Point, Return on Investment.